Kinetics of the transport of aerosol particles under the influence of drift forces in the standing wave field - CZYŻ, Henryka (Archives of Acoustics, 1987)
In the paper the time constants of the aerosol particles transport process under the influence of drift forces appearing in the standing wave field have been estimated. The transport phenomenon which causes particle concentration in the neighbourhood of the minimum of drift force potential significantly supports the coagulation microprocesses by reducing the distances between particles. It has been demonstrated that the growth of particle concentration around the points of stable equilibrium is exponential. The time constant of this growth was estimated and the formulae which precisely determine the time needed to obtain the assumed concentration increase have been derived. Parameters of spatial particle distribution in the equilibrium state and time necessary for reaching such distribution have been estimated under an assumption of lack of interactions between particles.